Polylactic acid oriented film and preparation method thereof
By blending the polyhydroxy fatty acid ester copolymer with polylactic acid resin and using a bidirectional stretching process to prepare a polylactic acid-oriented film, the existing films have solved the problems of high heat shrinkage and insufficient barrier performance in high temperature environments, and achieved both low heat shrinkage and high barrier performance.
Patent Information
- Application Number
- CN202411901496.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-03-11
AI Technical Summary
The existing polylactic acid-oriented film has a high heat shrinkage rate under high temperature environments, which cannot meet the needs of food packaging or industrial packaging. At the same time, the barrier properties of oxygen and water vapor are insufficient, which affects the shelf life of the product.
Polylactic acid-oriented films are prepared by blending the polyhydroxy fatty acid ester copolymer with polylactic acid resin and using a bidirectional stretching process. Combining the combination of crystalline and amorphous polyhydroxy fatty acid ester copolymers, the barrier properties and heat resistance of the film are enhanced.
It realizes the low heat shrinkage and high barrier properties of polylactic acid-oriented films, meets the use requirements in high temperature environments, and provides better protection for sensitive products.
Smart Images

Figure CN119592033A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer material films, and in particular relates to a polylactic acid oriented film and a preparation method thereof. Background Art
[0002] Polylactic acid (PLA), a biodegradable thermoplastic aliphatic semi-crystalline polyester derived from crops and plant straw, has been widely used in express packaging, disposable tableware, biomedicine and other fields due to its renewable resource characteristics and good biodegradability. However, the crystallization rate of PLA is slow, resulting in low crystallinity, which in turn affects the heat resistance of the product. In addition, PLA has poor toughness and high oxygen permeability, which limits its application in the field of packaging films.
[0003] Biaxial stretching is a film preparation process that stretches amorphous polymer sheets horizontally and longitudinally between the polymer glass transition temperature and the cold crystallization temperature. After biaxial stretching, the physical thickness of the polylactic acid sheet is reduced on a macroscopic level, and the polymer molecular chains are arranged in an orderly manner along the stretching orientation direction on a microscopic level, and the physical properties of the film are improved. For crystalline polymers, the crystallinity of the oriented film is greatly improved, so the barrier, optical, and mechanical properties of the film are significantly improved. However, after the biaxial stretching process, the thermal shrinkage rate of the biaxially oriented polylactic acid (BOPLA) film is significantly increased, which cannot meet the requirements of food packaging or industrial packaging in high temperature environments.
[0004] Patent CN118386581B proposed a solution, which is to construct PLA stereocomposite crystals by compounding left-handed and right-handed PLA, and to construct highly oriented hybrid shredded crystal structures by biaxial stretching during the spinning process, which significantly reduces the thermal shrinkage of PLA fibers in boiling water. Although the barrier properties of BOPLA film are much better than those of ordinary polylactic acid, BOPLA film may not provide sufficient barrier protection when used in the packaging of products that are sensitive to oxygen and water vapor, such as tea and medicines, making the products susceptible to oxidation, moisture, etc., shortening the shelf life of the products.
[0005] The present invention aims to solve the above problems, in order to provide a polylactic acid oriented film with low heat shrinkage and high barrier properties, which can meet the use requirements in high temperature environments and provide better protection for sensitive products. Summary of the invention
[0006] In view of the above problems existing in the prior art, the present application provides a polylactic acid oriented film and a preparation method thereof, which has low heat shrinkage performance and good water vapor and oxygen barrier properties.
[0007] To solve the above problems, the present invention provides the following technical solutions:
[0008] In a first aspect, the present application provides a polylactic acid oriented film, comprising the following raw materials: a polyhydroxyalkanoate copolymer, a polylactic acid resin, a thickener and a compatibilizer, a plasticizer, and a compounded antioxidant; wherein the polyhydroxyalkanoate copolymer comprises a polyhydroxyalkanoate copolymer P1 and a polyhydroxyalkanoate copolymer P2.
[0009] In one embodiment of the present application, a polylactic acid oriented film includes the following raw materials in parts by weight: 1-25 parts of a polyhydroxyalkanoate copolymer, 67-98 parts of a polylactic acid resin, 0.1-0.2 parts of a thickener and a compatibilizer, 1-5 parts of a plasticizer, and 0.1-0.2 parts of a compound antioxidant; the polyhydroxyalkanoate copolymer includes a polyhydroxyalkanoate copolymer P1 and a polyhydroxyalkanoate copolymer P2.
[0010] In one embodiment of the present application, a polylactic acid oriented film comprises the following raw materials in parts by weight: 0.5-20 parts of polyhydroxyalkanoate copolymer P1, 0.5-6 parts of polyhydroxyalkanoate copolymer P2, 67-98 parts of polylactic acid resin, 0.1-0.2 parts of thickener and compatibilizer, 1-5 parts of plasticizer and 0.1-0.2 parts of compound antioxidant.
[0011] In one embodiment of the present application, the content of the repeating structural unit of the polyhydroxyalkanoate copolymer P1 is greater than 90 mol %.
[0012] In one embodiment of the present application, the content of the repeating structural unit of the polyhydroxyalkanoate copolymer P2 is greater than 50 mol % and less than 90 mol %.
[0013] In one embodiment of the present application, the polyhydroxyalkanoate copolymer is a copolymer with polyhydroxybutyrate as the main component.
[0014] In one embodiment of the present application, the polyhydroxybutyrate is preferably poly 3-hydroxybutyrate.
[0015] In one embodiment of the present application, the poly 3-hydroxybutyrate can be selected from one or more of poly (3-hydroxybutyrate-3-hydroxyvalerate) (PHBV), poly (3-hydroxybutyrate-hydroxyhexanoate) (P3HB3HH), and poly (3-hydroxybutyrate-4-hydroxybutyrate) (P3HB4HB).
[0016] In one embodiment of the present application, the content of 3-hydroxybutyrate structural units in the polyhydroxyalkanoate copolymer P1 is greater than 94 mol %.
[0017] In one embodiment of the present application, the content of 3-hydroxybutyrate structural units in the polyhydroxyalkanoate copolymer P1 is greater than 97 mol %.
[0018] In one embodiment of the present application, the content of 3-hydroxybutyrate structural units in the polyhydroxyalkanoate copolymer P2 is greater than 50 mol % and less than 90 mol %.
[0019] In one embodiment of the present application, the melting temperature of the polylactic acid resin is 150-170°C.
[0020] In one embodiment of the present application, the content of dextrorotatory polylactic acid in the polylactic acid resin is 1-4 wt.%.
[0021] In one embodiment of the present application, the viscosity increasing and compatibilizing agent is an epoxy oligomer chain extender, for example, it can be selected from ADR4468.
[0022] In one embodiment of the present application, the plasticizer is a citrate compound, which can be selected from one or more of tributyl citrate (TBC) and acetyl tributyl citrate (ATBC).
[0023] In one embodiment of the present application, the compound antioxidant is a compound antioxidant of hindered phenols and phosphites, for example, it can be selected from one of Irganox B225 and Irganox B215.
[0024] In a second aspect, the present application provides a method for preparing a polylactic acid oriented film, comprising the following steps:
[0025] The polyhydroxyalkanoate copolymer and the polylactic acid resin are subjected to a dehumidification and drying pretreatment, and each raw material is weighed according to weight, and mixed in a high-speed mixer to obtain a blend;
[0026] The blended material is added into a twin-screw extruder for extrusion and granulation to obtain composite modified granules and perform dehumidification and drying treatment;
[0027] The dried composite modified pellets are melted and plasticized in a single screw extruder, extruded through a die head, cast and rolled to obtain a polylactic acid composite sheet;
[0028] The polylactic acid composite sheet is placed in a biaxial stretching device, and is simultaneously biaxially stretched at a predetermined rate and ratio to form, and then annealed and heat-set to obtain a polylactic acid oriented film.
[0029] In one embodiment of the present application, the blend is obtained by mixing for 1-10 minutes.
[0030] In one embodiment of the present application, the blend is obtained by mixing for 5 minutes.
[0031] In one embodiment of the present application, the operating temperature range of the twin-screw extruder is 100-180°C.
[0032] In one embodiment of the present application, the operating temperature range of the twin-screw extruder is set to 100°C, 130°C, 155°C, 160°C, 160°C, 165°C, 170°C, 170°C, 165°C, 160°C, and 160°C.
[0033] In one embodiment of the present application, the feeding rate of the twin-screw extruder is 10-20 kg / h.
[0034] In one embodiment of the present application, the temperature range of the single screw extruder is 160-180°C.
[0035] In one embodiment of the present application, the temperature of the single screw extruder is 170°C.
[0036] In one embodiment of the present application, the rotation speed of the single screw extruder is 40-60 rpm.
[0037] In one embodiment of the present application, the rotation speed of the single screw extruder is 50 rpm.
[0038] In one embodiment of the present application, the polylactic acid composite sheet is biaxially stretched to a thickness of 300 μm.
[0039] In one embodiment of the present application, the temperature of the biaxial stretching molding is 80-100°C.
[0040] In one embodiment of the present application, the rate of biaxial stretching is 50-150% / s.
[0041] In one embodiment of the present application, the ratio of biaxial stretching is (1-3)×(1-3).
[0042] In one embodiment of the present application, the temperature of annealing and heat setting is 110-130°C.
[0043] In one embodiment of the present application, the annealing and heat setting time is 1-3 minutes.
[0044] In one embodiment of the present application, in the annealing and heat setting step, the polylactic acid composite sheet shrinks in the MD direction and the TD direction.
[0045] In one embodiment of the present application, the shrinkage ratio is 5-10%.
[0046] Compared with the prior art, the present invention has the following beneficial effects:
[0047] The present invention prepares a polylactic acid oriented film by blending, modifying and orienting a polylactic acid resin and a polyhydroxyalkanoate copolymer, and adopts a combination of crystalline and amorphous polyhydroxyalkanoate copolymers. The amorphous polyhydroxyalkanoate copolymer with low viscosity has a toughening effect on polylactic acid, and the crystalline polyhydroxyalkanoate is distributed in crystals after film orientation, which not only improves the barrier performance together with the PLA crystal, effectively isolates water vapor and oxygen, but also acts as an anchor point to inhibit the thermal shrinkage of the film, enhances the heat shrinkage resistance, and in the heat setting process of biaxial orientation, the heat shrinkage rate of the film is further reduced by high-temperature annealing shrinkage treatment, so that the final product maintains high barrier properties while also showing excellent heat shrinkage resistance. This polylactic acid film can meet the needs of foods with high packaging temperatures, packaged foods that need secondary heating, secondary processing such as printing and heat sealing of the film, and other related application scenarios. BRIEF DESCRIPTION OF THE DRAWINGS
[0048] Figure 1 Schematic diagram of the internal structure of the polylactic acid oriented film of the present invention;
[0049] Figure 2 The water vapor and oxygen permeability diagrams of the films prepared in the examples and comparative examples;
[0050] Figure 3 The figure is a comparison of the heat resistance of the films prepared in the embodiment and the comparative example after annealing and heat shrinkage treatment;
[0051] Figure 4 The figures are the mechanical properties of the films prepared in the examples and comparative examples;
[0052] Figure 5 This is a graph showing the thermal shrinkage results of the film under different heat treatment conditions in Example 6. DETAILED DESCRIPTION
[0053] The following will provide a clear and complete description of the technical solutions in the embodiments of the present application in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all of the embodiments.
[0054] The "range" disclosed in this application is defined in the form of a lower limit and an upper limit, and a given range is defined by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundaries of the particular range. The range defined in this way can be inclusive or exclusive of the end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a range.
[0055] Unless otherwise specified, the percentages between liquids and liquids in the present invention are volume / volume percentages; the percentages between liquids and solids in the present invention are volume / weight percentages; the percentages between solids and liquids in the present invention are weight / volume percentages; and the rest are weight / weight percentages.
[0056] Example 1
[0057] A polylactic acid oriented film, and its preparation method is:
[0058] Step S1: Raw material pretreatment and blending
[0059] Various biodegradable resins were pre-treated by dehumidification and drying; the above raw materials were weighed according to the weight ratio, and then mixed with a high-speed mixer at a rotation speed of 1000 rpm for 5 minutes to obtain a blend.
[0060] The weight proportions of each raw material are as follows: 0.5 part of PHBV (containing 95 mol% 3HB) is selected from the polyhydroxyalkanoate copolymer P1, 0.5 part of P3HB4HB (containing 86 mol% 3HB) is selected from the polyhydroxyalkanoate copolymer P2, 1 part of TBC is selected as the plasticizer, 98 parts of polylactic acid resin LX575 (with a dextrorotatory polylactic acid content of 2% and a melting temperature of 160-170°C), 0.1 part of thickener and compatibilizer ADR-4468 and 0.1 part of antioxidant Irganox B225 are selected as the plasticizer.
[0061] Step S2: Extrusion granulation of blended raw materials
[0062] The blend obtained in step S1 is added to a twin-screw extruder for extrusion and granulation, and the temperature range of the extruder is set to: 100°C, 130°C, 155°C, 160°C, 160°C, 165°C, 170°C, 170°C, 165°C, 160°C, 160°C, the extruder speed is 150rpm, and the extruder feeding rate is 16kg / h to obtain composite modified pellets and dehumidify and dry them.
[0063] Step S3: Extrusion casting of composite modified pellets
[0064] The composite modified material after dehumidification and drying treatment is added into a single screw extruder for melt plasticization and extruded through a die head for casting and winding to form a thin sheet with a thickness of 300 μm. The melt extrusion processing temperature is set at 170° C. to obtain a polylactic acid composite sheet.
[0065] Step S4: Biaxial stretching of polylactic acid composite sheet
[0066] In the biaxial stretching equipment, the sheet was first placed at 90°C and preheated for 30 seconds, then subjected to synchronous biaxial stretching at a rate of 100% / s with a stretching ratio of 3×3. After orientation, it was then directly shaped at 120°C and taken out.
[0067] Example 2
[0068] The difference between Example 2 and Example 1 is that in step S1, the polyhydroxyalkanoate copolymer P1 is selected from 12 parts of PHBV (containing 97 mol% 3HB), the polyhydroxyalkanoate copolymer P2 is selected from 6 parts of P3HB4HB (containing 86 mol% 3HB), the plasticizer is selected from 2 parts of ATBC, the polylactic acid resin LX175 (dextrorotatory polylactic acid content 4%, melting temperature 150-160°C) is 80 parts, the viscosity increasing and compatibilizing agent ADR-4468 is 0.2 parts, and the antioxidant Irganox B225 is 0.15 parts. Then, a sheet is prepared according to steps S2 and S3. In step S4, it is preheated at 90°C for 30s, and synchronously biaxially stretched at a rate of 100% / s, with a stretching ratio of 3×3. After orientation, it is directly shaped at 110°C and taken out.
[0069] Example 3
[0070] The difference between Example 3 and Example 2 is that the polyhydroxyalkanoate copolymer P1 is PHBV (containing 95 mol % 3HB), and the other preparation process conditions are the same.
[0071] Example 4
[0072] The difference between Example 4 and Example 2 is that the polyhydroxyalkanoate copolymer P1 is P3HB3HH (containing 94 mol % 3HB), and the other preparation process conditions are the same.
[0073] Example 5
[0074] The difference between Example 5 and Example 1 is that in step S1, the polyhydroxyalkanoate copolymer P1 is selected from 20 parts of PHBV (containing 97 mol% 3HB), the polyhydroxyalkanoate copolymer P2 is selected from 5 parts of P3HB4HB (containing 86 mol% 3HB), the plasticizer is selected from 5 parts of ATBC, the polylactic acid resin LX575 (2% dextrorotatory polylactic acid content, melting temperature of 160-170°C) is 70 parts, the thickening and compatibilizing agent ADR-4468 is 0.2 parts, and the antioxidant Irganox B215 is 0.2 parts. Then, a sheet is prepared according to steps S2 and S3. In step S4, it is preheated at 90°C for 30s, and synchronously biaxially stretched at a rate of 100% / s, with a stretching ratio of 3×3. After orientation, it is directly shaped at 110°C and taken out.
[0075] Example 6
[0076] The difference between Example 6 and Example 5 is that the polylactic acid resin used is LX175 (dextrorotatory polylactic acid content 4%, melting temperature 150-160° C.), and the other preparation process conditions are the same.
[0077] Example 7
[0078] The composition of the sheet in Example 7 is the same as that in Example 6, with the only difference being that in step S4 of this embodiment, the sheet is preheated at 80°C for 30s, and is subjected to synchronous biaxial stretching at a rate of 50% / s with a stretching ratio of 2.5×2.5. After orientation, the sheet is directly shaped at 110°C and taken out.
[0079] Example 8
[0080] The composition of the thin film in Example 8 is the same as that in Example 6, and the film is oriented with the same preheating and orientation process. The only difference is that in step S4 of this embodiment, there is an annealing shrinkage treatment. The specific steps are: the oriented film is sent into the annealing chamber, the annealing temperature is 120°C, and the film is also subjected to heat shrinkage treatment in the MD (longitudinal) and TD (transverse) directions, the shrinkage rate is 7%, and the annealing time is 2 minutes.
[0081] Example 9
[0082] The film composition of Example 9 is the same as that of Example 6, and the film is oriented with the same preheating and orientation process. The only difference is that in step S4 of this embodiment, the process of annealing shrinkage and shaping treatment is different. The specific steps are: the oriented film is sent into the annealing chamber, the annealing temperature is 130°C, and the film is also subjected to heat shrinkage treatment in the MD (longitudinal) and TD (transverse) directions, the shrinkage rate is 10%, and the annealing time is 3 minutes.
[0083] In addition to Example 8 and Example 9, a more detailed annealing heat shrinkage treatment was performed on Example 6, and the specific process parameters are shown in Table 1.
[0084] Table 1
[0085] Annealing temperature / ℃ Annealing time / min Heat shrinkage treatment rate / % 110 1 5 120 2 7 130 3 10
[0086] Comparative Example 1
[0087] The polylactic acid resin LX175 (4% dextrorotatory polylactic acid content, melting temperature of 150-160°C) was directly used to prepare the wire, and the PLA sheet was prepared through the S3 step, which was then preheated at 80°C for 30s, and synchronously biaxially stretched at a rate of 100% / s with a stretching ratio of 3×3. After orientation, it was directly shaped at 110°C and taken out.
[0088] like Figure 1As shown, the crystalline polyhydroxyalkanoate is distributed in crystals after film orientation. While acting as a barrier phase with the PLA crystals, it can also become an anchor point to inhibit the thermal shrinkage of the oriented polylactic acid film.
[0089] The oxygen permeability and water vapor permeability coefficient of the above comparative examples and embodiments were measured at 23°C and 50% RH. The test results are shown in Figure 2 ,from Figure 2 It can be seen that when A-poly 3-hydroxybutyrate copolymer uses PHBV and P3HB3HH with a higher 3HB molar content, as the amount of addition increases, the water vapor permeability and oxygen permeability coefficient of the oriented film both decrease significantly. This is because when the 3HB molar content in the poly 3-hydroxybutyrate copolymer is high, its crystallinity is also high. During the orientation process, the polylactic acid molecular chain tends to be regular and is more prone to oriented crystallization. Therefore, the overall crystallinity of the film is high, and the permeation paths of water vapor and oxygen inside the film become more tortuous. Therefore, the water vapor and oxygen barrier properties of the composite film are greatly improved. However, the coefficient changes of Example 6 and Examples 7-9 are not obvious. The comparative example and each example were then placed in an oven at 100°C for 10 minutes, and the dimensional changes were recorded. Figure 3 It can be seen from the figure that compared with the comparative example, when adding a poly 3-hydroxybutyrate copolymer with a higher 3HB molar content, the heat resistance of the film can be appropriately improved and its thermal shrinkage rate can be reduced. After the film is subjected to thermal shrinkage treatment during the orientation process, the heat resistance of the film is significantly improved, which is specifically manifested in that its thermal shrinkage rate is significantly reduced. At the same time, the shrinkage rate of the film prepared at a ratio of 2.5×2.5 is also significantly lower than that of the sample prepared at 3×3. The experimental results of the annealing temperature, annealing time and shrinkage rate parameters of the shrinkage treatment process in Example 6 show that Figure 5 It can also be found that the actual thermal shrinkage rate of the oriented polylactic acid film product is positively correlated with the annealing process parameters in Table 1, which can be appropriately adjusted in actual production to obtain a composite film with optimal heat resistance.
[0090] Therefore, it can be seen that in the orientation process, in the heat setting step after the film is oriented, the heat resistance of the film product in actual use can be significantly improved by appropriately heat shrinking the film. The film was then tested for mechanical properties, and it can be seen that the rigidity and toughness of the film can be adjusted by selecting poly 3-hydroxybutyrate copolymers with different 3HB molar ratios to prepare a polylactic acid composite oriented film with excellent mechanical properties.
[0091] The present application is described in detail above in conjunction with specific implementation methods and exemplary embodiments, but these descriptions cannot be understood as limiting the present application. Those skilled in the art understand that, without departing from the spirit and scope of the present application, the technical solution of the present application and its implementation methods may be subjected to a variety of equivalent substitutions, modifications or improvements, all of which fall within the scope of the present application.
Claims
1. A polylactic acid oriented film, characterized in that: The invention comprises the following raw materials in parts by weight: 1-25 parts of polyhydroxyalkanoate copolymer, 67-98 parts of polylactic acid resin, 0.1-0.2 parts of viscosity increasing and compatibilizing agent, 1-5 parts of plasticizer and 0.1-0.2 parts of compound antioxidant; the polyhydroxyalkanoate copolymer comprises polyhydroxyalkanoate copolymer P1 and polyhydroxyalkanoate copolymer P2; the content of repeating structural units of the polyhydroxyalkanoate copolymer P1 is greater than 90 mol%, and the content of repeating structural units of the polyhydroxyalkanoate copolymer P2 is greater than 50 mol% and less than 90 mol%.
2. The polylactic acid oriented film according to claim 1, characterized in that: The polyhydroxyalkanoate copolymer is a copolymer with polyhydroxybutyrate as the main component; the polyhydroxybutyrate is selected from one or more of poly 3-hydroxybutyrate-3-hydroxyvalerate, poly 3-hydroxybutyrate-hydroxycaproate, and poly 3-hydroxybutyrate-4-hydroxybutyrate.
3. The polylactic acid oriented film according to claim 1, characterized in that: The polyhydroxyalkanoate copolymer P1 has a 3-hydroxybutyrate structural unit content of greater than 94 mol %.
4. The polylactic acid oriented film according to claim 1, characterized in that: The melting temperature of the polylactic acid resin is 150-170° C., and the content of dextrorotatory polylactic acid in the polylactic acid resin is 1-4 wt.%.
5. The polylactic acid oriented film according to claim 1, characterized in that: The viscosity increasing and compatibilizing agent is an epoxide chain extender; the plasticizer is a citrate compound; and the compound antioxidant is a compound antioxidant of hindered phenols and phosphites.
6. The method for preparing a polylactic acid oriented film according to any one of claims 1 to 5, characterized in that: The following steps are involved: S1: performing dehumidification and drying pretreatment on the polyhydroxyalkanoate copolymer and the polylactic acid resin, weighing each raw material by weight, and mixing them in a high-speed mixer to obtain a blend; S2: adding the blended material to a twin-screw extruder for extrusion and granulation to obtain a composite modified pellet and performing dehumidification and drying treatment; S3: melting and plasticizing the dried composite modified pellets in a single screw extruder, extruding, casting and rolling through a die head to obtain a polylactic acid composite sheet; S4: placing the polylactic acid composite sheet in a biaxial stretching device, biaxially stretching the sheet at a predetermined rate and ratio, and then annealing and heat setting to obtain a polylactic acid oriented film.
7. The method for preparing a polylactic acid oriented film according to claim 6, characterized in that: The processing temperature range of the twin-screw extruder is 100-180° C., and the feeding speed is 10-20 kg / h.
8. The method for preparing a polylactic acid oriented film according to claim 6, characterized in that: The temperature range of the single screw extruder is 160-180° C., and the rotation speed is 40-60 rpm.
9. The method for preparing a polylactic acid oriented film according to claim 6, characterized in that: The temperature of biaxial stretching is 80-100°C, the speed is 50-150% / s, the ratio is (1-3)×(1-3), the temperature of annealing and heat setting is 110-130°C, and the time of annealing and heat setting is 1-3min.
10. The method for preparing a polylactic acid oriented film according to claim 9, characterized in that: During the annealing heat setting process, the film is shrunk in the MD and TD directions, with a shrinkage ratio of 5-10%.
Citation Information
Patent Citations
Special polyhydroxyalkanoate film blowing material and film
CN118222074A
High-performance polylactic acid biaxially oriented film and preparation method thereof
CN118813008A
Stretched film and method for producing same
WO2023090176A1
Method for producing stretched film
WO2024203640A1
Biodegradable resin composition, biodegradable film using same, and method for producing same
WO2024215088A1